A Review: Role of Aldosterone in Hypertension - Audu, Jankada Patience; Chikata, Ezugwu Hilary; Ipav, Selumun Solomon; Umaru, Isaac John; Iseko, Kingsley Iyoko; Istifanus, Dafup Katdel (African Journal of Biochemistry and Molecular Biology Research, 2024)
In Western societies, hypertension affects up to 20% of the population, making it a significant public health concern. The rates of blood pressure control remain unsatisfactory despite advancements in treatment. Since hypertension is a complex disorder, there is rarely a single, obvious cause identified for so-called "essential" hypertension. The primary mineralocorticoid in humans, aldosterone is increasingly understood to contribute significantly to cardiovascular morbidity. Its role in hypertension has also been examined in view of recent research suggesting that up to 15% of hypertensive individuals exhibit a key phenotype of increased aldosterone biosynthesis, as indicated by an elevated aldosterone to renin ratio. Excessive production or activity of mineralocorticoids is a significant contributing factor to secondary hypertension. Humans' basic mineralocorticoid is aldosterone, and when an aldosterone-secreting adenoma (Conns tumour) is linked to primary aldosterone excess, it can be surgically treated. Although primary aldosteronism was once thought to be rare, recent studies have reported preval_ence rates of up to 20% among hypertensive patients. This reflects the increasing use of the plasma aldosterone concentration to renin activity ratio (ARR), which is a proxy for angiotensin II, the major trophic substance regulating aldosterone secretion. Traditionally, patients with Conns tumour present with spontaneous hypokalaemia and have a relative excess of aldosterone production with suppression of plasma levels of renin (a proxy for angiotensin II, the major trophic substance regulating aldosterone secretion).